PROGRAM BANTUAN STIMULUS KEMENTERIAN PEKERJAAN UMUM DAN PERUMAHAN RAKYAT DI KECAMATAN XIII KOTO KAMPAR - Ikrami Waldi; Geovani Meiwanda (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
In order to improve the quality of life and welfare of the public through residential and healthy settlements, harmonious and safe to be needed the improvement of quality to slum and self 2018-reliance housing through the Ministry of Public Assisted housing stimulant assistance is the government facilitation of stimulant aid for low-income communities for the development/improvement of home quality to low-income communities. The phenomenon in this study is yet to in fact the beneficiaries of stimulant self-help housing, has not appropriately targeted the beneficiaries and lack of supervision of a self-help stimulant aid program. The purpose of this research is to know how the effectiveness of a self-help stimulant assistance Program in District XIII Koto Kampar and to know the inhibitory factor of the effectiveness of these self-housing stimulant aid programs. This research was conducted in the district XIII Koto Kampar using qualitative descriptive methods, collected data collected through observation and interviews. The research was conducted using the theory of effectiveness by Makmur, consisting of timeliness, accuracy of cost calculations, accuracy of measurement, accuracy in determining options, accuracy of thinking, accuracy of doing orders, precision determining the objectives and accuracy of determining the target. The conclusion of this research is, the independent housing stimulant assistance Program in District XIII Koto Kampar is still not effective. It is shown that there are still many people who support self-help on the program. This is because the effort done in the program is not maximal in terms of supervision and authority. Keywords : Effectiveness, Self-reliance Programs